Peng aruh Pemberian Insentif Dan Penempatan Karyawan Ter hadap Kinerja Karyawan Divisi P enjualan Di Pt.United Motors Centre Gresik The Effect Of Giving Incentive And Employee Placement On Employee Performance Insales Division At Pt. United Motors Centre - Azizah, Imroatul; S, Sasongko; Wahyuni, Sri (University of Jember, 2019)
AbstractDealer Banyuwangi Motor is a company engaging in the service sector, especially in providing and selling motor vehicles (Honda brand) for consumers. Incentive contains a professional relationship. The employee'sgoals to work areto fulfill the employees' life needs, and to implement the company's mission and vision. Therefore, employees will be rewarded in the form of incentivewhich is suitable with their work performance and companyRequirements.This researchwas aimed to know the effect of incentive on sales employees’work performance at Dealer Banyuwangi Motor in Genteng. The amount of incentive given by the company to sales employees was based on the achieving target level in each month with each sales position. Sales employees’ work performance was seen from the quantity achieved that was the target which exceeded the company's requirements and the task execution by providing product information from the company to prospective customers. This quantitativeresearchemployed explanative approach.39 respondents were determined by using simple linear regression analysis. The measurement technique in this researchwas likert scale. The data were analyzed by using validity test, reliability test, simple linier regression analysis, hypothesis test, and coefficient of determination (R2). The research results indicated that incentive had a significant effect on sales employees’ work performance at Dealer Banyuwangi Motor in Genteng. Hypothesis value test obtained that incentive value had tcount> ttable (2,357> 2,026), and the significance value was 0,024 <0,05. Therefore, H0 was rejected, and Ha was accepted. The Coefficient Value (R2) of Incentive variable (X) to Work Achievement (Y) variable was equal to 0.131. This value indicated that incentive affected work performance as much as 13.1% while the remaining 86.9% was influenced by other factors excluded in this research.Keywords:Incentive, Work Performance, and Sales Employees